Transcriptional activation by TAL1 and FUS-CHOP proteins expressed in acute malignancies as a result of chromosomal abnormalities. - Isidro Sánchez‐García; Terence H. Rabbitts (1994)
Proteins that appear to participate in transcriptional control of gene expression are increasingly implicated in leukemias and malignant solid tumors. We report here that the N-terminal domains of the proteins TAL1 (ectopically activated in T-cell acute leukemias after chromosomal abnormalities caused by V-D-J recombinase error) (V, variable; D, diversity; J, joining) and FUS-CHOP (a liposarcoma tumor-specific fusion protein that is produced as a result of a chromosomal translocation) can function as transcription activators of specific responsive reporter genes. The result with TAL1 provides evidence that transcriptional activation can be mediated by a gene activated by translocation in T-cell acute leukemias. In the case of the liposarcoma, transactivation by the FUS-CHOP protein occurs because the FUS transcriptional activation domain is added to the DNA-binding CHOP protein normally lacking such activity. Therefore, the association of transcriptional activation and DNA-binding elements is a common consequence in proteins activated or newly created as fusion proteins after chromosomal translocations in acute leukemias and in malignant solid tumors.